MARICULTURE BASED ON THROPIC SAPROBIC INDEX ANALYSIS (Case Study: Coast of Sayung Distric Demak, Central Java Indonesia) - Sri Rejeki; agung Suryanto; Johanes Hutabarat; Sutrisno Anggoro; R usmilyansari (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Coastal erosion in Sayung Distric, Demak Regency submerged 300 hectares of brackish water ponds. However, after the local government management by soft and hard barriers construction resulting the formation of semi-closed coastal water area with the depth of 1 – 7 m in depth. The condition of the this eroded coastal water is physically degraded, idle and abandont. The aims of this research were to evaluate ecological condition of the eroded coastal water at Sayung for coastal aquaculture based on its Trophic Saprobic Index values. The research was carried out from September 2009- August 2010. The results show that the eroded coastal water at Morosari, Sayung District Demak Central Java is lightly to moderately polluted, however, ecol[ogically it is still suitable for coastal aquaculture activity, especially for cultured organisms which are at the lowest level of the food chain/the plankton feeder .